Themes in peace psychology research - Noor, Noraini M.; Christie, Daniel J. (Springer, 2015)
This chapter identifies some concepts, themes and theories in peace psychology based on a selection of relevant articles and books that examine the psychological components of peace, conflict, and violence. To organize the literature, first, we use the 2 x 2 matrix that distinguishes between episodic and structural violence and peace. Then, we identify some concepts, themes and theories that fit neatly within each of the four cells of the matrix. We also identify other psychologically-based concepts, themes and theories that are more highly integrative and can be applied to at least two cells of the matrix: either episodic and structural violence or episodic and structural peace. At the most integrative level, we identify concepts, themes and theories in peace psychology that can be applied to all four cells in the matrix. We further extend the two dimensional 2 x 2 matrix and add a third dimension that distinguishes between the objective and subjective properties of violence and peace. Then, we examine the inter-connectedness of violence and peace from a systems perspective in which violence and peace are viewed as the interplay of concepts and processes across individual, relational, and structural levels of analysis. We acknowledge that the experience of peace and violence varies with geo-historical contexts, and accordingly, we highlight some of the focal concerns of scholars in various regions of the world. Finally, we conclude the chapter by noting that from a global perspective, sustainable peace requires the continuous crafting of socially just ends through nonviolent means.